2012
DOI: 10.6061/clinics/2012(05)12
|View full text |Cite
|
Sign up to set email alerts
|

Obese elderly women exhibit low postural stability: a novel three-dimensional evaluation system

Abstract: OBJECTIVE:The aim of this study was to evaluate the multisegmental static postural balance of active eutrophic and obese elderly women using a three-dimensional system under different sensory conditions.METHODS:A cross-sectional study was conducted on 31 elderly women (16 eutrophic and 15 obese) aged 65 to 75 years. The following anthropometric measurements were obtained: weight, height, waist and hip circumference, and handgrip strength. The physical activity level was evaluated using the International Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
2
21
0
6
Order By: Relevance
“…Realizar com facilidade, sem auxílio de terceiros gestos motores, como segurar um copo de água, subir um lance de escadas, sentar-se, entre outros, sem que haja o risco de quedas, demonstra autonomia para realizar tarefas do dia a dia, fato este que acresce uma melhor qualidade de vida 20,26 . [28][29][30] . Alta prevalência de excesso de gordura corporal é um fator alarmante, pois está diretamente relacionada a uma má condição de saúde como alterações do perfil lipídico, o aumento da pressão arterial e a hiperinsulinemia, além dos fatores de risco para o desenvolvimento de doenças crônicas, como o diabetes tipo 2 e as doenças cardiovasculares, entre outras 15,31 .…”
Section: Discussionunclassified
“…Realizar com facilidade, sem auxílio de terceiros gestos motores, como segurar um copo de água, subir um lance de escadas, sentar-se, entre outros, sem que haja o risco de quedas, demonstra autonomia para realizar tarefas do dia a dia, fato este que acresce uma melhor qualidade de vida 20,26 . [28][29][30] . Alta prevalência de excesso de gordura corporal é um fator alarmante, pois está diretamente relacionada a uma má condição de saúde como alterações do perfil lipídico, o aumento da pressão arterial e a hiperinsulinemia, além dos fatores de risco para o desenvolvimento de doenças crônicas, como o diabetes tipo 2 e as doenças cardiovasculares, entre outras 15,31 .…”
Section: Discussionunclassified
“…These findings indicate that a high BMI is associated with reduced postural control and balance after a TKR. Because being overweight or obese is a risk factor for poor postural stability (56)(57)(58), and because changes in body weight influence balance control (59,60), it is reasonable to expect that overweight and obese patients perform more poorly in the FRT and SLS test compared with patients with a normal BMI, because such tasks are highly dependent on postural stability and balance control. Previous studies have shown that the performance of postural stabilitydependent mobility tasks improves after balance-based post-TKR rehabilitation (24,38), which is consistent with the significant improvements in the FRT and SLS test results for all of the BMI groups at the 2-month and 6-month post-TKR followup assessments in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 By means of signals obtained from the sensors, deviations in the x (anterior-posterior [AP]), y (medial-lateral [ML]), and z (vertical) planes can be measured. [10][11][12][13][14] The Polhemus device precisely measures all trunk movements through its transmitter coil, which emits an electromagnetic field that is detected by the sensor. The device was calibrated before each evaluation by placing the transmitter coil on a hard level surface, shifting it forward 2cm, and assessing the accuracy of the system in measuring the displacement.…”
Section: Methodsmentioning
confidence: 99%